THE EFFECT OF ONLINE TRAINING, MOTIVATION & LEADERSHIP ON JOB SATISFACTION IN IMPROVING EMPLOYEE PERFORMANCE - Magalhaes, Cancio Andhika Irawan; Sutarso, Yudi (Universitas Islam Lamongan, 2024)
This study aims to obtain empirical evidence of employee job satisfaction as a moderator of the effect of online motivation, motivation and leadership on employee performance with employee job satisfaction as a moderator. The dependent variable in this study is employee performance, the independent variables in this study are online training, motivation and leadership, while the moderating variable in this study is employee job satisfaction. The research was conducted on employees of PT. Bank Rakyat Indonesia Sidoarjo Branch Office in 2023. This type of research is quantitative. The data in this study used primary data by distributing questionnaires. The sampling method uses purposive sampling. The data analysis technique used is Moderated Regression Analysis (MRA). The results of this study indicate that there is a significant positive effect on employee job satisfaction which moderates online training, motivation and leadership on employee performance. The results of this study are expected to help the management of PT. Bank Rakyat Indonesia Sidoarjo Branch Office in knowing the effect of increasing the performance and job satisfaction of BRI Sidoarjo branch employees.